Analysis of subsidised fertiliser distribution efficiency using the lean thinking approach following the implementation of the zero ODOL policy: A case study of deliveries to Bojonegoro Regency - Hally Hanafiah; Adhito Prabowo; Muhammad Ihsan; Tony Hendra Prasetya; Tony Kristhiofan; Mokhtar Abdullah (OPSI, 2026)
The Zero Over Dimension Overload (Zero ODOL) policy, regulated by Minister of Transportation Regulation No. 60 of 2019, significantly impacted fertiliser distribution, decreasing truck transport capacity by 47%. This raised costs from Line I to Line III Bojonegoro Warehouse to Rp 26.2 billion annually. This study identifies inefficiencies and improvements using Lean Thinking with tools like Pareto Analysis, Ishikawa Diagram, and 5w+2 h. Manual loading and unloading caused waste through waiting, unproductive movements, defects, and repetition. The solution adopts pallets and forklifts to cut reliance on labour. Validated through a one-month operational pilot project managing 2,370 tonnes of fertiliser, Lean implementation structurally improved efficiency: logistics costs dropped to Rp 21 billion (20% savings), loading/unloading speed tripled from 250 to 750 tonnes/day, fertiliser damage reduced to 0.002%, and quantitative stakeholder satisfaction increased significantly. Lean delivers cost savings and enhances quality, safety, and sustainability amidst Zero ODOL challenges.